Current Trends in Translation - Maylath, Bruce (Communication & Language at Work, 2013)
Driven by the growth of a global economy and developments in high technology, the process of creating and translating technical documentation has been evolving rapidly. In particular, machine translation (MT) has shown increasing capabilities of efficaciously accomplishing the early stages of the eight stages of translation identified years ago by Robert Bly. As a consequence, translators have learned to use MT as a tool to accelerate their work, but they have also grown wary of MT’s potential for replacing them. To ensure steady employment, some translators have begun cross-training as technical writers; correspondingly, a few technical writers have begun cross-training as translators, as the two professions appear to be undergoing a gradual trend of convergence. Academic programs are urged to respond to the evolving trends.